Aplicação do método dos elementos discretos em simulações envolvendo a termologia - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Computer simulations have become a great ally of engineers, being a low cost and risk way, and the finite element method has positioned itself as the most used. However, in cases coupled to failure the discrete element, the method becomes an interesting tool . The understanding of failure in structures subjected to the action of large thermal gradients, such as fire, becomes a problem of high complexity and importance. With the perspective of this academic work, the search for the feasibility of the application and representative factors in the study of the method of discrete elements together with thermology, also in search of useful ways for research and expansion of knowledge in this environment. Bibliographic review methods were used along with computational analyzes in the Abaqus software, in addition to different formulations developed for this purpose. A simulation was carried out in the Abaqus/explicit, Abaqus/Standart environment and analytical calculations, which were sought to be compared for validation. In the results of this research, consistency of the method related to simulations involving expansion and thermal rupture can be noted, and inconsistency in the methodology regarding heat transfer was located and pointed out, where due to restrictions of the software used, it was not possible to perform them as expected.In conclusion, I proved the initial failure of our hypotheses, which did not allow validation by our methodology. It was possible to suggest new studies turns to the heat transfer line, where it is believed that simulations through for Fortran to have good results, in addition to self-criticism, where it was possible to further study
Keywords: Engenharia mecânica; Método dos elementos discretos; Termologia; Abaqus (recurso eletrônico); Mechanical engineering; Discrete elements method; Thermology; Abaqus (Electronic resource); CNPQ::ENGENHARIAS